Mobility And Behavior Influences On Import Malaria In The Kecamatan Watulimo Kabupaten Trenggalek - Asep Prastiawan (Universitas Airlangga, 2019)
Malaria is becoming the most widely distributed disease in the world. There were 212 million cases of malaria and 429,000 of them died in the year 2015. Enviromental, behavior, knowledge and health care factors play an important role in the incidence of malaria in endemic areas. The purpose of this study was analyze the influence of mobility and behavioral factors on malaria import incidence in the Kecamatan Watulimo, Kabupaten Trenggalek. This research was an observational, used case control study design. The research samples were 42 people. Data were statistics analyzed using logistic regression test. The results of this research were influence between high frequency of mobility (p=0.023; OR=16.670), duration of stay in endemic areas for a bit (p=0.014; OR=35.940), less knowledge (p=0.022; OR=11.946), and less practice (p=0.010; OR=25.534) against malaria import incidence in the Kecamatan Watulimo, Kabupaten Trenggalek. But there was not influence attitude (p=0.470) against malaria import incidence in the Kecamatan Watulimo, Kabupaten Trenggalek. The high frequency of mobility factor â‰¥ 3 times and duration of stay in endemic areas for a bit 1-2 months, behavior factor less knowledge and practice can lead to increased risk of malaria import incidence in the Kecamatan Watulimo, Kabupaten Trenggalek. We recommended to increased the community knowledge and practice on malaria and its prevention with counseling. Increased JMD empowerment, revitalization of Posmaldes, provision of chemoprophylaxis malaria and insecticide mosquito net at the village level.